Importance of reporting ancillary site characteristics, and management and disturbance information at ICOS stations - Saunders, M.; Dengel, S.; Kolari, P.; Moureaux, C.; Montagnani, L.; Ceschia, E.; Altimir, N.; López Ballesteros, A.; Marañon Jimenez, S.; Acosta, M.; Klumpp, K.; Gielen, B.; et al. (Walter de Gruyter GmbH, 2018)
There are many factors that influence ecosystem scale carbon, nitrogen and greenhouse gas dynamics, including the inherent heterogeneity of soils and vegetation, anthropogenic management interventions, and biotic and abiotic disturbance events. It is important therefore, to document the characteristics of the soils and vegetation and to accurately report all management activities, and disturbance events to aid the interpretation of collected data, and to determine whether the ecosystem either amplifies or mitigates climate change. This paper outlines the importance of assessing both the spatial and temporal variability of soils and vegetation and to report all management events, the import or export of C or N from the ecosystem, and the occurrence of biotic/abiotic disturbances at ecosystem stations of the Integrated Carbon Observation System, a pan-European research infrastructure.